2014
DOI: 10.1589/jpts.26.219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trunk Stabilization Exercises Using a Sling on the Balance of Patients with Hemiplegia

Abstract: [Purpose] The purpose of this study was to examine the effects of trunk stabilization exercise using a saing on the balance ability of patients with hemiplegia. [Subjects] Forty patients with hemiplegia resulting from stroke were divided into a sling exercise group (SEG, n=20) and a mat exercise group (MEG, n=20). [Methods] The SEG conducted the trunk stabilization exercise using a sling, and the MEG performed the trunk stabilization exercise on a mat. [Results] The balance ability of both groups significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 8 publications
2
33
0
1
Order By: Relevance
“…In younger participants, Kim et al (2013) showed a significant sway speed reduction of 23%. Beyond that, after eight weeks of sling training, COP sway length for normal stance significantly decreased by about 30% (Park, Hwangbo, 2014). In a study by Prokopy et al (2008), a 12-week sling training induced single-leg stance performance enhancements of 57% and 65% for COP sway area.…”
Section: Discussionmentioning
confidence: 93%
“…In younger participants, Kim et al (2013) showed a significant sway speed reduction of 23%. Beyond that, after eight weeks of sling training, COP sway length for normal stance significantly decreased by about 30% (Park, Hwangbo, 2014). In a study by Prokopy et al (2008), a 12-week sling training induced single-leg stance performance enhancements of 57% and 65% for COP sway area.…”
Section: Discussionmentioning
confidence: 93%
“…This is more efficient, and comfortable relative to the traditional exercise [42]. Intriguingly, Hwangbo and Lehman reported that, sensorimotor training on an unstable surface along with muscle stimulation improve the joint proprioception [11] [43] This is owing to the substantial effect of sensorimotor on improvement of muscles control and joints stability along with facilitating their normal response restoration [4] [44]. Another efficient tool for providing unstable surface during SET, is through deployment of foam mats, tilt board, Swiss balls, and air-filled rubber cushions ascribed to their effect on enhancement muscles' stress and activation and improvement of joint Proprioception [45].…”
Section: Balance and Sensorimotor Trainingmentioning
confidence: 95%
“…Various sling suspension systems models that were developed over the past century. Open/close kinetic chain Feasible for using both of Open/close kinetic chain exercises [10] Sensorimotor/balance Enhance balance and proprioceptive [4] [11] Stabilizing system Increase the durability of the joints and muscles during training [12]- [15] Muscle training Vulnerable for applying various simultaneous exercises for multi-muscles [16]- [22] Relax/relief pain Decrease pain along with enhance muscles relaxation [4] [8] [15] Diagnostics Weak link testing Facilitates detection of the impairments between the deep stabilizer and superficial prime mover muscles [23] Holding time Examination the stability of the deep muscles under neutral position [24] adults which are always requiring highly complicated, costly, and inefficient therapeutic methods. Alternatively, SET possesses many advantages for LBP over the other approaches due to its considerable effect on muscles and nerves [29].…”
Section: A Brief History Of Setmentioning
confidence: 99%
“…SE is also known as a treatment strategy to improve balance adjustment and functional outcome in various clinical quantities17, 18 ) . This study was able to demonstrate the effects of SE on the balance of post-stroke patients and the effects of SE on various functional measurements, especially quantitative balance performance.…”
Section: Discussionmentioning
confidence: 99%